ANALISIS PEMETAAN BUDAYA ORGANISASI MENGGUNAKAN ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT PADA PT. BANK PEMBANGUNAN DAERAH JAWA TENGAH - Anggun Tri Febriana; Ahyar Yuniawan (Faculty of Economics and Business Diponegoro University, 2013)
A demands of change in the business world is a threat that can not be avoided anymore. Regional Development Bank of Central Java Limited Company is one of the many companies that decide to make changes in order to maintain their existence. Management Change Program was announced by the Bank Jateng since 2005 and followed up in 2011 by reaching out to employees as partners for change. This Cultural transformation made an effort in realizing the next vision and mission of Bank Jateng, one of his vision is to become BPD Regional Champion in 2014. Therefore, the mapping of cultural organization that aims to analyze the current organizational culture profile and the next five years at Regional Development Bank of Central Java Limited Company to facilitate the process of cultural transformation that was planned. The study used a survey method with the Organizational Culture Assessment Instrument (OCAI). The survey was conducted on directors, division chief, branch chief, and partner for change in the level of employees with a quantitative and qualitative (descriptive) approach, aims to reveal and analyze the cultural profile of the current Bank Jateng and the next five years. The results of this study, there is a common perception among directors, division chief, branch chief, a partner of change in the employee level which stated that the cultural profile of the current Bank Jateng is a hierarchy. However, on the next five years they are expected to have a combination of different cultures. Directors and chief of the division expects a combination of market and hierarchy cultures. Branch heads and partners of change, expect the combination of cultural change between the clan and a market cultural that is expected in the next five years. Alternatives market cultural dimensions to be the main focus in the next five years refers to the management of employees as a dimension that is expected to be more improve. Based on the interpretation of the cultural mapping, showing some indication that is: the process of cultural transformation from an organizational traditional hierarchical design to a modern organization design, Big expectations in five years ahead of Bank Bank Jateng has been in line with their goals become BPD Regional Champion 2014, and the role of Java culture in formation of organizational culture in the Bank Jateng.Key words: Transforming Organizational Culture, Organizational Culture Mapping, OCAI, Quantitative Descriptive